2010
DOI: 10.1177/02601079x10002200304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Pollution on Peri-Urban Agriculture in Varanasi, India

Abstract: Air pollution reduces both the yield and nutritional quality of the farm produce. Phytotoxic gases have been found to cause major yield reductions on a range of important crops in the developing countries. The present study estimates the yield loss in the major corps of peri-urban areas due to air pollution. All the major corps like Paddy, Pigeon-pea, Maize, Wheat and Potato grown in the peri-urban areas have shown yield reductions due to air pollution in the city Varanasi, India. There is a need to carry out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The intensive agriculture facilities are one of the important source of heavy metals along urbanization, industrialization and transportation and these metals affect the surrounding environment (Falandysz et al, 2007). A significant phytotoxic effect of different air pollutants including heavy metals was seen on different crops such as paddy, pigeon pea, maize, wheat and potato by Sen (2010). According to Suganya et al (2016), all metals, even essential and trace, becomes toxic for the animal body and environment when present in excessive amount.…”
Section: Resultsmentioning
confidence: 99%
“…The intensive agriculture facilities are one of the important source of heavy metals along urbanization, industrialization and transportation and these metals affect the surrounding environment (Falandysz et al, 2007). A significant phytotoxic effect of different air pollutants including heavy metals was seen on different crops such as paddy, pigeon pea, maize, wheat and potato by Sen (2010). According to Suganya et al (2016), all metals, even essential and trace, becomes toxic for the animal body and environment when present in excessive amount.…”
Section: Resultsmentioning
confidence: 99%
“…Tidblad et al (2016) showed the results of research on various corroded materials at 10 locations in Kathmandu (Nepal) related to SO 2 , NO 2 , O 3 , HNO 3 , and PM concentrations and climatic factors, and compared the results with a general pattern from exposures at different sites in Asia, Africa, and Europe [20]. Air pollution also affects wildlife and reduces both the yield and nutritional quality of farm produce [22]. Rai (2016) reviews harmful effects of PM pollution (as an effective indicator of the overall impact of air pollution) on vegetation, covering an extensive span of 1960 to 2016 [23].…”
Section: Ligus Mmentioning
confidence: 99%